Methods of operational and strategic logistics control and their role in managerial decision making - Nikolaievska, Alina; Bohdanov, Serhii (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The purpose of this research is the theoretical justification of logistic control as a factor in making managerial decisions. Design/methodology/approach. The following research methods were used in the work: comparative, systemic, description. Findings. The research topic is caused by rapid changes in the consumer market. They are connected with the transitional character of the Ukrainian economy and the integration processes with the European Union. Effective use of logistics control methods allows to remain competitive in the new environment. The subject of research are the causes and features of the application of methods of operational and strategic control. The article presents the key tasks of logistics control and characterizes the main tools of strategic management. The article analyzes the methods of operational control by establishing their advantages and disadvantages. The model of the integrated system of operational logistics management is also proposed in the research. On the basis of the conducted research the conclusion about economic expediency of introduction of systems of logistical management is made. At the same time, it is necessary to take into account the technological and organizational features of enterprises. Research limitations/implications. In-depth study of methods of operational and strategic logistics control will increase the efficiency and expand the scope of their application in enterprises of any type. Originality/value. The results of studies of the various logistics control methods will be the basis for further researches in this area. They will also help to develop an algorithm for implementation of the integration model of logistics control into enterprises